DNA damage signaling mediates the functional antagonism between replicative senescence and terminal muscle differentiation - Latella, Lucia (Genes Dev, 2017)
The molecular determinants of muscle progenitor impairment to regenerate aged muscles are currently unclear. We show that, in a mouse model of replicative senescence, decline in muscle satellite cell-mediated regeneration coincides with activation of DNA damage response (DDR) and impaired ability to differentiate into myotubes. Inhibition of DDR restored satellite cell differentiation ability. Moreover, in replicative human senescent fibroblasts, DDR precluded MYOD-mediated activation of the myogenic program. A DDR-resistant MYOD mutant could overcome this barrier by resuming cell cycle progression. Likewise, DDR inhibition could also restore MYOD's ability to activate the myogenic program in human senescent fibroblasts. Of note, we found that cell cycle progression is necessary for the DDR-resistant MYOD mutant to reverse senescence-mediated inhibition of the myogenic program. These data provide the first evidence of DDR-mediated functional antagonism between senescence and MYOD-activated gene expression and indicate a previously unrecognized requirement of cell cycle progression for the activation of the myogenic program.